2016
DOI: 10.18632/oncotarget.10291
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tissue and circulating microRNA expression during metaplastic transformation of the esophagus

Abstract: Genetic changes involved in the metaplastic progression from squamous esophageal mucosa toward Barrett's metaplasia and adenocarcinoma are almost unknown. Several evidences suggest that some miRNAs are differentially expressed in Barrett's esophagus (BE) and esophageal adenocarcinoma. Among these, miR-143, miR-145, miR-194, miR-203, miR-205, miR-215 appear to have a key role in metaplasia and neoplastic progression. The aim of this study was to analyze deregulated miRNAs in serum and esophageal mucosal tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“… 49–51 Of note, circulating levels of group 2 miRNAs were elevated during the development of BO compared with those in healthy controls ( figure 3B ). Cabibi et al 52 also reported that tissue and circulating miR-143-3 p levels are elevated during metaplastic transformation of the oesophagus, suggesting that group 2 miRNA may be associated with intestinal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“… 49–51 Of note, circulating levels of group 2 miRNAs were elevated during the development of BO compared with those in healthy controls ( figure 3B ). Cabibi et al 52 also reported that tissue and circulating miR-143-3 p levels are elevated during metaplastic transformation of the oesophagus, suggesting that group 2 miRNA may be associated with intestinal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Luzna P et al [13] proposed that miR-192 and miR-196a were up-regulated with an increase during BE progression. Cabibi D et al [17] found increased expression levels of miR-143, miR-145, miR-194 and miR-215 in BE, while miR-203 and miR-205 were down-regulated. Wijnhoven B P et al [19].…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous miRNAs interact with the 3'-UTR of target mRNA to suppress post-transcription of genes [5,6]. Previous studies have underscored the relevance of miRNAs as potential biomarkers for disease diagnosis, cancer prediction and prognosis assessment, including BE and EAC [10,11,13,15,[17][18][19][20]22,[29][30][31][32][33]. These studies mostly focused on BE carcinogenesis and were less concerned with its pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs are a group of endogenous non-coding RNA molecules that act as negative regulators in post-transcriptional gene regulation. Recent studies reported that aberrant miRNA expression is associated with the development of BE ( 30 , 31 ). The current study found five differentially expressed miRNAs, including two upregulated DEmiRNAs and three downregulated DEmiRNAs.…”
Section: Discussionmentioning
confidence: 99%